The Glocalization Process of Shin Buddhism in Brasilia - Matsue, Regina Yoshie (Journal of Religion in Japan, 2014)
The glocalization process of Shin Buddhism in Brasilia is the focus of this article. The first part of this work presents a historical and sociological overview of the introduction and settlement of Shin Buddhism in Brazil, and the second part examines the specificities of the contemporary temple situation in Brasilia. This paper illustrates how external cultural inflows interact and negotiate with daily local actions and demand and thus acquire a distinctive connotation at the local level. However, due to the mixture of local cultural elements in interaction with imported ones the processes of appropriation and transformation may allow the emergence of something new and unique. In the glocalization of Shin Buddhist practices in Brasilia the work of innovation and articulation conducted by some members of the clergy has been fundamentally important. Especially, the clergy have understood the demand for self-cultivation practices coming from a larger audience and incorporated meditation in the temple space.